PENGARUH KADAR AIR AWAL TERHADAP PERTUMBUHAN JAMUR DAN KONTAMINASI AFLATOKSIN PENYIMPANAN JAGUNG - Yunianta Yunianta; Khusnan Khusnan; Ali Agus; Nuryono Nuryono; Zuprizal Zuprizal (Fakultas Pertanian, Universitas Janabadra, 2013)
Agricultural products tropical countries generally sensitive to fungal growth and aflatoxin contamination. Research evaluate fungal growth and Aflatoxin B1 production on corn with different level of beginning moisture content at different storage length. Corn sample taken from farmer in Tulung Distric, divided nine sacs 60 kg respectively, sun dried to get moisture content 13, 15, and 18 percent. Each group stored six months. Sample 300 g per sac from each group taken every month, analyzed aflatoxin B1 content, fungus spore’s and colony, A. flavus identification and counted of moisture and starch content. Aflatoxin B1 content significantly differences, highest aflatoksin B1 content in 18 percent. Fungal spore’s growth during first month of storage and grow fast until fourth month. Highest fungal spores during storage was in 18 percent. Moisture content during storage showed significantly differences, while starch not significant. From microscophis identification A. flavus showed that 60.32 percent samples infected, especially during storage. Importance moisture contend at drying stage to control fungal growth and further AFB1 production. Key-words: corn; moisture; aflatoxin. INTISARIProduk pertanian negara tropis sensitif terhadap pertumbuhan jamur dan kontaminasi aflatoksin. Penelitian ini mengevaluasi pertumbuhan jamur dan produksi Aflatoksin B1 jagung dengan tingkat kadar air awal dan lama penyimpanan berbeda. Sampel jagung diambil dari petani, dibagi sembilan kantung 60 kg, dengan pengeringan matahari untuk mendapatkan kadar air 13, 15, dan 18 persen. Lama penyimpanan enam bulan. Sampel 300 g per kantung diambil setiap bulan, dianalisis kadar aflatoksin B1, spora jamur dan koloni, A. flavus identifikasi dan dihitung dari kelembaban dan kadar pati. Kadar aflatoksin B1 berbeda signifikan, kadar aflatoksin B1 tertinggi dalam 18 persen. Spora jamur tumbuh selama bulan pertama penyimpanan dan tumbuh subur sampai bulan keempat. Spora tertinggi berada di 18 persen. Total koloni tertinggi juga pada kadar air 18. Kadar air selama penyimpanan menunjukkan perbedaan yang bermakna, sedangkan pati tidak signifikan. Hasil identifikasi microscophis A. flavus menunjukkan 60.32 sampel persen terinfeksi, terutama selama penyimpanan. Perlu kelembaban bersaing pada tahap pengeringan untuk mengontrol pertumbuhan jamur dan produksi AFB1 lanjut. Kata kunci: jagung, kelembaban, aflatoksin.